Fiscal policy, housing and stock prices - António Afonso; Ricardo M. Sousa (European Central Bank (ECB), 2009)
This paper investigates the link between fiscal policy shocks and movements in asset markets using a Fully Simultaneous System approach in a Bayesian framework. Building on the works of Blanchard and Perotti (2002), Leeper and Zha (2003), and Sims and Zha (1999, 2006), the empirical evidence for the U.S., the U.K., Germany, and Italy shows that it is important to explicitly consider the government debt dynamics when assessing the macroeconomic effects of fiscal policy and its impact on asset markets. In addition, the results from a VAR counter-factual exercise suggest that: (i) fiscal policy shocks play a minor role in the asset markets of the U.S. and Germany; (ii) they substantially increase the variability of housing and stock prices in the U.K.; and (iii) government revenue shocks have apparently contributed to an increase of volatility in Italy.
Keywords: C32; E62; G10; H62; 330; Bayesian Structural VAR; Fiscal Policy; housing prices; stock prices; Finanzpolitik; Immobilienpreis; Börsenkurs; Bayes-Statistik; VAR-Modell; Deutschland; Großbritannien; Italien; USA